(untitled) (Fiep Bulletin - online, 2014)
Bus equipment with deficiencies in design and construction, associated with other factors, such as vibration, forced postures for prolonged periods of time, duration of bus-driver profession, length of working day, leads to work-related damage to health in bus drivers continuously exposed to the risk-producing source. To evaluate the influence of the workstation upon workrelated sickness in bus drivers. The epidemiological cross-sectional descriptive and inductive study included 200 bus drivers working for five different companies of urban transport in Osasco, SP. Study subjects were asked to fill out a form, the questions being used as study variables. Study results are presented as percentages and absolute numbers in simple frequency graphs and tables. The present study complied with ethical and legal requirements. 48% of study subjects had worked as bus drivers for more than 9 years; 66% of study subjects worked 8 to 12 hours daily; 52.5% presented pain radiating down the legs with 11.26% and 9.22% reporting sporadic leg and lumbar pain, respectively, while 7.20% and 11.20% reported continuous leg and lumbar pain, respectively; 29.5% reported pain radiating down the upper limbs with 9.56%, 2.05%, and 6.48% reporting sporadic pain in the shoulders, hands, arms, respectively, while 8.0%, 1.60%, and 7.20% reported continuous pain in the shoulders, hands, and arms, respectively. Study results suggest that bus driver’s cabin with deficiencies in design and construction leads to musculoskeletal disorders and, as a consequence, to decreased performance, specially when associated with prolonged 242 exposure to external factors.